The Abundance of Microplastics in Sediment Siak River Pekanbaru City - Tasya Anaya Dzaki Khalis; Ternala Alexander Barus; Hesti Wahyuningsih (Jurnal Penelitian Pendidikan IPA, 2024)
Sediments are temporary and long-term reservoirs for waste including microplastic particles.  Microplastics are large-sized plastics that are under 5mm in size. microplastic particles with a density greater than water can enter the sediment and accumulate. High water utilization activities can be a way for plastic waste from land to enter the waters, one of the rivers that has high utilization is the Siak River in Pekanbaru city. This study aims to analyze the abundance and distribution of microplastics based on 3 (three) stations in the Siak River. The research procedure consists of sampling, microplastic separation, and microplastic analysis. The results showed that the Siak River in Pekanbaru city contained microplastic types of fragments (32%), films (31%), fibers (25%), and granules (12%). The highest abundance of microplastics was at station 1 with an average abundance of 32.67/kg which was dominated by fragment-type microplastics. The Siak River in Pekanbaru city has been contaminated with microplastics which can be intentionally or unintentionally eaten by aquatic biota.